RENEWABLE ENERGY IN INTERNATIONAL LAW: RUSSIAN PERSPECTIVE FOR DEVELOPING THE COMMON BRICS APPROACH - Alexander N. Vylegzhanin; Dmitry V. Ivanov; Maria A. Milyukova (Publishing House V.Ема, 2023)
The growing influence of renewable energy in the global economy raises concerns about perfecting the relevant international legal regime to satisfy all the stakeholders concerned. This paper analyzes the relevant legal position of Russia as one of the largest exporters of energy-related products focusing on cooperation within BRICS. The research suggests a number of key findings: Russia has so far cautiously supported the promotion of renewable energy internationally; nevertheless, it has demonstrated a very restrained approach to the development of legally binding instruments on the matter. The authors conclude that it is viable to find a reasonable “compromise of compromises” for the evolving international legal regime of renewable energy, and BRICS might become a leading international place for creating such a legal regime.